Pathogenic Events in a Nonhuman Primate Model of Oral Poliovirus Infection Leading to Paralytic Poliomyelitis - Shen, Ling (J Virol, 2017)
Despite a great deal of prior research, the early pathogenic events in natural oral poliovirus infection remain poorly defined. To establish a model for study, we infected 39 macaques by feeding them single high doses of the virulent Mahoney strain of wild type 1 poliovirus. Doses ranging from 10(7) to 10(9) 50% tissue culture infective doses (TCID(50)) consistently infected all the animals, and many monkeys receiving 10(8) or 10(9) TCID(50) developed paralysis. There was no apparent difference in the susceptibilities of the three macaque species (rhesus, cynomolgus, and bonnet) used. Virus excretion in stool and nasopharynges was consistently observed, with occasional viremia, and virus was isolated from tonsils, gut mucosa, and draining lymph nodes. Viral replication proteins were detected in both epithelial and lymphoid cell populations expressing CD155 in the tonsil and intestine, as well as in spinal cord neurons. Necrosis was observed in these three cell types, and viral replication in the tonsil/gut was associated with histopathologic destruction and inflammation. The sustained response of neutralizing antibody correlated temporally with resolution of viremia and termination of virus shedding in oropharynges and feces. For the first time, this model demonstrates that early in the infectious process, poliovirus replication occurs in both epithelial cells (explaining virus shedding in the gastrointestinal tract) and lymphoid/monocytic cells in tonsils and Peyer's patches (explaining viremia), extending previous studies of poliovirus pathogenesis in humans. Because the model recapitulates human poliovirus infection and poliomyelitis, it can be used to study polio pathogenesis and to assess the efficacy of candidate antiviral drugs and new vaccines. IMPORTANCE Early pathogenic events of poliovirus infection remain largely undefined, and there is a lack of animal models mimicking natural oral human infection leading to paralytic poliomyelitis. All 39 macaques fed with single high doses ranging from 10(7) to 10(9) TCID(50) Mahoney type 1 virus were infected, and many of the monkeys developed paralysis. Virus excretion in stool and nasopharynges was consistently observed, with occasional viremia; tonsil, mesentery lymph nodes, and intestinal mucosa served as major target sites of viral replication. For the first time, this model demonstrates that early in the infectious process, poliovirus replication occurs in both epithelial cells (explaining virus shedding in the gastrointestinal tract) and lymphoid/monocytic cells in tonsils and Peyer's patches (explaining viremia), thereby supplementing historical reconstructions of poliovirus pathogenesis. Because the model recapitulates human poliovirus infection and poliomyelitis, it can be used to study polio pathogenesis, candidate antiviral drugs, and the efficacy of new vaccines.